Transforming teaching in health: Exploring the advantages of the Flipped Classroom Active Methodology (Research, Society and Development, 2023)
The use of active methodologies in health education has effectively contributed to the teaching and learning process in both corporate settings and educational institutions, leading to the effectiveness in developing the knowledge, skills, and attitudes required for healthcare professionals. For this reason, the objective of this study was to explore the literature on the challenges of implementing the active methodology of flipped classroom in health education and to identify the necessary skills for educators to apply this methodology in teaching. This qualitative research utilized an integrative review approach to investigate the use of active methodologies, particularly the flipped classroom, which gained prominence after the shift to emergency remote teaching during the pandemic, with institutions adapting to hybrid teaching models. The results indicate that investing in teacher training for the use of Information and Communication Technology (ICT) to support learning, as well as developing effective strategies for flipped classroom implementation, are necessary. Moreover, updating the curricula of health education institutions with more active and innovative methodologies is crucial. Therefore, conducting further research to demonstrate the outcomes of applying the flipped classroom methodology in healthcare education is essential to foster its dissemination in educational institutions.